Premature Cell Senescence and T Cell Receptor–Independent Activation of CD8+ T Cells in Juvenile Idiopathic Arthritis. Issue 8 (26th July 2013) - Dvergsten, Jeffrey A.; Mueller, Robert G.; Griffin, Patricia; Abedin, Sameem; Pishko, Allyson; Michel, Joshua J.; Rosenkranz, Margalit E.; Reed, Ann M.; Kietz, Daniel A.; Vallejo, Abbe N.
Abstract : Objective: CD8+ T cells lacking CD28 were originally reported to be a characteristic feature of juvenile idiopathic arthritis (JIA), but the relevance of these unusual cells to this disease remains to be elucidated. Because of recent evidence that loss of CD28 cells is typical of terminally differentiated lymphocytes, the aim of this study was to examine functional subsets of CD8+ T cells in patients with JIA. Methods: Blood and/or waste synovial fluid samples were collected from children with a definite diagnosis of JIA (n = 98). Deidentified peripheral blood (n = 33) and cord blood (n = 13) samples from healthy donors were also collected. CD8+ and CD4+ T cells were screened for novel receptors, and where indicated, bioassays were performed to determine the functional relevance of the identified receptor. Results: JIA patients had a naive T cell compartment with shortened telomeres, and their entire T cell pool had reduced proliferative capacity. They had an overabundance of CD31+CD28 null CD8+ T cells, which was a significant feature of oligoarticular JIA (n = 62) as compared to polyarticular JIA (n = 36). CD31+ CD28 null CD8+ T cells had limited mitotic capacity and expressed high levels of the senescence antigens histone γH2AX and/or p16. Ligation of CD31, which was independent of the T cell receptor (TCR), sufficiently induced tyrosine phosphorylation, vesicle exocytosis, and production of interferon‐γ and interleukin‐10. Conclusion: These data provide the first evidence of cell senescence, as represented by CD31+CD28 null CD8+ T cells, in the pathophysiology of JIA. Activation of these unusual cells in a TCR‐independent manner suggests that they are maladaptive and could be potential targets for immunotherapy.